The Effect of Cognitive Behavioral Therapy Group Counseling on the Well-Being of Self-Harming Emerging Adults - Gayoles, Lisa Anna M.; Magno, Janette Raissa A. (Philippine Social Science Journal, 2020)
This study determined the effect of Cognitive Behavioral Therapy (CBT) group counseling on the psychological well-being of self-harming emerging adults. It utilized the pretest-posttest control group design. The Self-Harm Inventory (SHI) was used to determine self-harming emerging adults. There were no significant relationships among the socio-demographic variables and the level of severity of self-harm of 30 college students. The intervention was a four session CBT group counseling. The Depression, Anxiety, and Stress Scale – 21 (DASS-21) was used to measure psychological well-being. There were eight participants in the experimental group and nine participants in the control group. The results of the study revealed significant differences in the psychological well-being of the experimental group and the control group after the intervention. The findings suggest implications in school guidance and counseling programs to address the mental health issues of emerging adults.